Identifying diabetes risks among Indonesians: A cross-sectional study in a community setting - Mula Tarigan; Setiawan; Rosina Tarigan; Fatwa Imelda; Darunee Jongudomkarn (Belitung Nursing Journal, 2024)
Background: There is an upward surge in diabetes patients worldwide, including in Indonesia, annually. Diabetes can lead to new diseases that burden patients’ lives further. Nurses can reduce this problem by identifying people at risk of developing diabetes and educating them on how to prevent diabetes. Objective: The study aimed to determine the risk of diabetes in the Indonesian population. Methods: The descriptive research involved a sample of 1216 Indonesians living in North Sumatra Province. Participants were nondiabetic individuals selected using the convenience method from May to October 2020. This study utilized the Indonesian version of the Finnish Diabetes Risk Score (FINDRISC) tool and employed various statistical analyses, including frequencies, percentages, chi-square test, and Fisher’s exact test. Results: Of the total samples, 372 were males (30.6%), and 844 were females (69.4%). The risk of developing diabetes was classified as low (57.1%), slightly elevated (36.4%), moderate (5.3%), high (1.0%), and very high (0.2%). Only one of the eight risk factors that differed significantly between men and women was a history of elevated blood glucose levels, with a p-value of 0.02. Conclusion: The study identified a portrait of the number and percentage of diabetes risk factors in a community setting in Indonesia. Nurses must provide education on diabetes prevention to not only members of the local community at the research site but also the general public, nationally and globally.